2018
DOI: 10.1007/s40257-018-0360-y
|View full text |Cite
|
Sign up to set email alerts
|

Daylight Photodynamic Therapy for Actinic Keratoses

Abstract: Topical photodynamic therapy (PDT) using daylight is effective in the treatment of actinic keratoses (AKs), offering the potential for treatment of large fields such as full face and balding scalp, but with minimal therapy-associated pain. Comparison with conventional PDT indicates similar efficacy for thin and moderate-thickness AKs, but with significantly less discomfort/pain, driving a patient preference for daylight-mediated PDT (DL-PDT) compared with conventional PDT using high-intensity office/hospital-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 68 publications
1
29
0
Order By: Relevance
“…In addition, pain and discomfort caused by red-light PDT can be significantly reduced using daylight PDT to treat precancerous skin lesions. 5 Daylight skin PDT can be performed using sunlight (>4-8 J/cm 2 ), but light devices are necessary for internal tumours, and for skin cancer in poor sunlight. 4 Lasers as PDT light sources offer high power output and easy connection to optical fibres and endoscopes, with precise light delivery to tumours in internal organs.…”
Section: Mainmentioning
confidence: 99%
“…In addition, pain and discomfort caused by red-light PDT can be significantly reduced using daylight PDT to treat precancerous skin lesions. 5 Daylight skin PDT can be performed using sunlight (>4-8 J/cm 2 ), but light devices are necessary for internal tumours, and for skin cancer in poor sunlight. 4 Lasers as PDT light sources offer high power output and easy connection to optical fibres and endoscopes, with precise light delivery to tumours in internal organs.…”
Section: Mainmentioning
confidence: 99%
“…It has been demonstrated that daylight can be sufficient to allow MAL-PDT to function; the effects of weather conditions, season, and latitude have been assessed, showing the potential of daylight-mediated PDT (DL-PDT). It is now a frequent method of topical PDT for superficial precancerous skin lesions, i.e., thin-moderate actinic keratoses (AK) of the head and neck [68]. The use of DL-PDT for BCC has been investigated in a case series of 21 patients/32 lesions, where, after the application of MAL but, unlike conventional PDT, without an intervening period of occlusion, the BCC were exposed for 2.5 h to daylight.…”
Section: Light Sources For Pdtmentioning
confidence: 99%
“…As the time required to penetrate the skin is much longer during the cPDT process, the applied photosensitizers are mainly located in deep tissue where cutaneous nerves are found, which causes moderate to severe pain [29]. It seems that dPDT results in patient satisfaction because of the almost zero pain as well as excellent cosmetic results upon treatment [30,31]. Next, Ferrario et al suggested that targeting survivin, a Hsp-90 client protein, possibly improves PDT responses [32].…”
Section: Erdr1 and Photodynamic Therapymentioning
confidence: 99%